On θg**- Closed Sets in Topological Spaces : θg**-closed Sets - Alrikabiu, Ahmed Hussain Wajaean; Hussain, Ali Khalaf Hussain (Wasit Journal of Computer and Mathematics Science, 2023)
In this paper we have introduced a new class of closed in topological spaces called g**-closed sets and study some of its properties . Further we introduce the concept g**-continuous functions , g**-irresolute functions . As an application we introduce two news paces namely . T **-space, **T - space .Further, g**-continuous, and g**-irresolute mappings are also introduced and investigated .